Controles e resistências no processo de informatização da Corte de Justiça Pernambucana (1983-1992). - Cavalcanti, João Carlos Gonçalves (2020)
The process of informatization of Pernambuco’s Judiciary Power (PJPE) took place in the 1980’s, moment in which companies and public agencies such as Companhia de Eletricidade de Pernambuco (Celpe), Companhia Pernambucana de Saneamento (Compesa), Departamento de Trânsito (Detran) and the Secretaria de Administração do Estado, amongst others, adopted electronic data processing to modernize the services offered to Pernambuco’s society. The presidency of the State’s Court obtained financial resources with the State’s Government so that the Centro de Prestação de Serviços Técnicos de Pernambuco (Cetepe) would develop and implement a computerized system destined to distribute and keep in check the lawsuits that moved around Recife’s county courts. In december of 1986, the system, named Infojus, started operating. The informatization of the Palace of Justice, however, started in the year of 1988 with the acquisition of the license for the use of softwares from a private informatics company, with the system being implemented by the end of July of 1989. The modernization, represented by a new work method combined with the use of technological resources under the sponsorship of Pernambuco’s Court of Justice leaders, found resistance by part of PJPE’s judges and public servers. Nevertheless, the informatization of the services came to be, supported by legal measures that coerced the opposing actions to this goal.